The Effect of Service Quality, Customer Orientation and Customer Satisfaction on Customer Loyalty - Situmeang, Samuel; Sugiyanto, Sugiyanto (PT Inovasi Pratama Internasional, 2024)
This study aims to examine the effect of service quality, customer orientation on customer satisfaction and customer loyalty on JCO products. This study is motivated by unmentioned customer loyalty, so a study was conducted to find out from the quality of service and customer orientation which will be the most influential variables on customer satisfaction and customer loyalty on JCO products. The population in this study were all consumers at JCO Outlets domiciled in the Jabotabek area, totaling 103 Outlets. While the research sample was taken using a purposive sampling technique, namely customers who had purchased JCO products at least 2 times with a total of 170 respondents. This research is a quantitative study using the Structural Equation Model - Partial Least Square (SEM-PLS) method. The results of the study indicate that customer orientation has a positive effect on service quality, followed by the following hypotheses, namely service quality has a positive effect on customer satisfaction, customer orientation has a positive effect on customer satisfaction, service quality has a positive effect on customer loyalty, but customer orientation does not have a positive effect on customer loyalty, customer satisfaction has a positive effect on customer loyalty, service quality does not mediate customer orientation on customer satisfaction, in contrast to customer satisfaction mediating service quality and customer orientation on customer loyalty. After conducting the study, the author suggests adding other supporting variables, such as product quality, word of mouth promotion, brand trust, price and various other variables that are relevant to the novelty of the study. In the future, JCO is expected to be able to improve service quality and customer orientation in terms of responding to customers with polite language in responding to complaints from customers so that JCO customers will feel happy and become more loyal in buying JCO products.